The Ural region on the agricultural front (1941–1945) Review of Motrevich, V.P. Vklad v Pobedu: sel'skoe khozyaistvo Urala v gody Velikoi Otechestvennoi voiny [A contribution to the Victory: Agriculture of the Urals during the Great Patriotic War]. Yekaterinburg: Al'fa print, 2021. - Vladimir N. Mamyachenkov (Historia provinciae: журнал региональной истории, 2022)
The author reviews the monograph by the famous Ural historian Vladimir P. Motrevich, which is devoted to an important and relevant topic. It is emphasized that the monograph analyses the entire range of issues related to the state and dynamics of the development of the agrarian sector of the Ural region in the extreme period of the USSR’s history. The issues considered in the monograph are related to the material and technical base of the regional agricultural sector in the context of farming and stockbreeding, its two most important areas, as well as labor resources, living conditions of rural workers, etc. At the same time, the leitmotif of the study is the activity of authorities at all levels – from local to all-union authorities – in the field of agricultural production management.